Fuzzy Programming Approach for Solving Intuitionistic Fuzzy Linear Fractional Programming Problem - Singh, Sujeet Kumar; Yadav, Shiv Prasad (International journal of fuzzy systems, 2016)
This paper develops an approach for solving intuitionistic fuzzy linear fractional programming problem (IFLFPP). The cost of the objective function, the resources, and the technological coefficients are taken to be triangular intuitionistic fuzzy numbers. Here, the IFLFP problem is transformed into an equivalent crisp multi-objective linear fractional programming problem (MOLFPP). By using fuzzy mathematical programming approach, the transformed MOLFPP is reduced into a single objective linear programming problem (LPP) which can be solved easily by suitable LPP algorithm. The proposed procedure is illustrated by a numerical example.